The Effect of Competence and Work Environment on Employee Performance (Study at PT. PLN (Persero) Main Unit for Distribution of Kalimantan Load Regulatory Funds (UIP3B Kal) - Muhammad Feriansyah; Sulastini Sulastini; Maskur Maskur (Cita Konsultindo Research Center, 2023)
This study aims to, Determine the significant influence of partial competence on employee work. Knowing the significant influence of the work environment partially on employee performance. Knowing the significant influence of competence, work environment simultaneously on employee performance at the office of PT PLN (Persero) Kalimantan Distribution and Load Control Main Unit (UIP3B Kal). The analysis method uses multiple linear regression equations. The population in this study is individual employees who are still actively working in the study population is all employees at the office of PT PLN (Persero) Kalimantan Distribution and Load Management Main Unit (UIP3B Kal). The study sample was 52 people. Partial testing of the Effect of Competency on employee performance, amounted to 6.67, Thus, the hypothesis stating that Competence has a positive and significant effect on employee performance at the office of PT PLN (Persero) Kalimantan Distribution and Load Management Main Unit (UIP3B Kal) proved to be accepted. The effect of the work environment on the value of t calculated environmental variables is 16.30, thus partially the environment has a significant influence on employee performance at the PT office. PLN (Persero) Kalimantan Distribution and Load Management Main Unit (UIP3B Kal) proved acceptable. The effect of competence, work environment simultaneously on the calculated t value is 83.61, thus simultaneously having a significant influence on employee performance at the PT office. PLN (Persero) Kalimantan Distribution and Load Management Main Unit (UIP3B Kal) proved acceptable Keywords: Competence, Working environment, performance